Effective capture of gaseous Se during spent nuclear fuel recycling using calcium oxide pellets: Optimization, performance, and practical implications - Seok-Min Hong; Chang Hwa Lee; Jae-Hwan Yang; Namcheol Kim (Nuclear Engineering and Technology)
The continuous utilization of nuclear energy has led to the accumulation of spent nuclear fuel (SNF) containing uranium, transuranium, and fission products (FPs). Reprocessing and pyrochemical methods have shown the potential for SNF reuse, thereby reducing its environmental impact. Voloxidation, a pivotal step in SNF recycling, involves thermal treatment in an oxidizing atmosphere to enhance the reactivity. During voloxidation, Se-79, which is a FP with a long half-life, is released as SeO2 under oxidizing conditions, necessitating technologies to capture it. CaO pellets (CPs) were prepared to capture gaseous SeO2. The effects of operating conditions on SeO2 capture performance were investigated. The CP reacts strongly with SeO2 to form CaSeO3, exhibiting a high adsorption capacity of 17.5 mol kg−1 and >99 % efficiency at 700 °C. The mechanical strength and thermal stability assessments indicate suitability for practical applications. Depending on the flow rate, the CP required for SeO2 capture was estimated when processing 1 t of SNF, thereby contributing to the design of effective SeO2 capture systems for safe and sustainable nuclear waste management.